Length of Stay and Frequency of Visits in Chiangkhan (in Thai) - Nakornthab, Arm; Chancharat, Surachai (Asian Journal of Applied Economics, 2013)
This paper presents the analysis of tourism demand in Chiangkhan, Loei province. Travelcost method (TCM) with Poisson regression was applied to analyze factors affecting thedecision of tourists as to the number of nights they would stay in Chiangkhan. The analysisincludes logistic regression to consider the variables that affect the decision to revisit.The respondents were Thai tourists visiting Chiangkhan subdistrict. The data from 856respondents were collected in January-February and June-July 2011 using a structuredinterview form. The respondents were impressed and attracted most by the ambience, cultureand traditional living style. Young tourists from Bangkok with medium level of incomecomprised the most number of visitors. Those who had visited Chiangkhan would likely decideto revisit. However, the decision to revisit had an inverse relation to their income level. Thetourism strategy should encourage the demand for tourism of the target group and aim topreserve the culture and tradition of Chiangkhan. Keywords: Tourism demand, length of stay, revisiting, Chiangkhan JEL Classification: C31, L83